Temperature and Weight Dependence of Free Volumes in Conducting Composite Polymer Using Positron Annihilation Techniques - (:unkn) unknown (WALTER DE GRUYTER & CO, 2011)
Polyvinylidene fluoride-co-hexafluoropropylene (PVdF-co-HFP) with conducting polyaniline (PAni) was studied to measure free-volume intensity (I(3)), orthopositronium (o-Ps) lifetime (tau(3)), and Doppler momentum distribution parameters (S and W) as a function of temperature varying from 273 to 373 K and PAni weight percentage varying from 1 %-20 % using the techniques of Positron Annihilation Lifetime Spectroscopy (PALS) and Doppler Broadening Annihilation Radiation (DBAR). It has been observed that the free-volume intensity and the o-Ps lifetime increased sharply with PAni weight percentage up to 4 % after which decreased slowly. DBAR momentum distribution parameters behaved similarly as well and it's assumed that in the studied samples one-type defect was to exist. The thermal expansion coefficient also as a function of PAni weight was extracted from PALS data.
Keywords: Positron annihilation lifetime spectroscopy; free volume; conducting polymers; PAni; PVdF-co-HFP; thermal expansion coefficient; POLYANILINE; LIFETIME; BLENDS; FILMS